O violão na canção de câmara brasileira: um estudo de seus aspectos musicais e simbólicos - Claudia Araujo Garcia (2011)
The guitar in the Brazilian chamber song: a study about its musical and symbolic features. This work consists in the musical and symbolical features that involve the guitar usages in the Brazilian art song. By recognizing the intrinsic connection of this instrument with the popular music, especially as a vocal accompanist in two important means of expression of our culture the modinha and the seresta , we dedicated to study how (and whether) this guitar, their contexts, musical aspects and symbolisms reverberated in the classical music. In order to do so we relied on the historical musicology and on the repertoire analysis, seeking to refer not just to musical parameters, but to the resignification processes as well, which led the guitar, between hybridities and cultural exchanges, from the controversial instrument, related to bohemia, to an emblem of national identity. Foremost, we investigated how the guitar has taken part of two important Brazilian genre´s configuration: the modinha and the lundu. Next, we ascertained how the guitar was present in some nationalists pieces for the singing and piano, through the version of its sonority and seresta feature, once this instrument for its bad consideration did not have its own space recognized in Brazilian sphere until the beginning of the twentieth century. Ultimately, in addition to approach its path as soloist and the implications from this change of role such as the development of new resources, spaces, interpreters and repertories , we also opposed and analyzed pieces originally written for singing and guitar. Putting history and song together, it was possible to comprehend more properly, as from some Heitor Villa-Lobos, César Guerra-Peixe, Francisco Mignone and Osvaldo Lacerdas pieces, how the guitar arranged itself among dialogs, conflicts and symbologies in the accompaniment of Brazilian art song.